Hardball - Nides, Tina; Tollin, Mike; Robbins, Brian (Hollywood, Ca. : Paramount, 2002)
A down-on-his-luck gambler finds himself in debt to a dangerous loan shark. Desperate for cash, he reluctantly takes on the job of coaching a youth baseball team. The team turns out to be a ragtag group of tough-talking kids from Chicago's inner city. Now, as he must wrestles with his past, the kids start to teach him some lessons that will forever change his future
Executive producer, Kevin McCormick ; editor, Ned Bastille ; screenplay, John Gatins
Cast: Keanu Reeves, Diane Lane, John Hawkes, D. B. Sweeney
VCD format
Keywords: Children in motion pictures; Sports in motion pictures